Living Conditions and Psychological Distress in Latino Migrant Day Laborers: The Role of Cultural and Community Protective Factors. Issue 1 (20th December 2016) - Organista, Kurt C.; Ngo, Samantha; Neilands, Torsten B.; Kral, Alex H.
Abstract: The purpose of this study was to examine the relationship between typically difficult living conditions and psychological distress in Latino migrant day laborers (LMDLs), with attention to the potentially protective roles of contact with family in country of origin (i.e., communication, sending money, etc.), availability of local culture (i.e., food, music, people from one's country of origin), and utilization of community resources perceived to be culturally competent (i.e., services that are respectful, able to serve Latinos, able to solve problems, in Spanish, etc.). Participants were 344 LMDLs surveyed in the San Francisco Bay Area. As hypothesized: (a) difficult living conditions were related to depression, anxiety, and desesperación [desperation], the latter a popular Latino idiom of psychological distress recently validated on LMDLs; (b) contact with family moderated the relation between difficult living conditions and depression and desesperación but not anxiety and (c) access to local culture, and utilization of community resources, mediated the relation between difficult living conditions and depression and desesperación but not anxiety. Implications for intervening at local and larger levels in order to provide some protection against distress built into the LMDL experience in the United States are discussed.